Preferencje mieszkańców Białegostoku względem leśnych usług rekreacyjnych – potrzeba odmienności krajobrazowej - Smoleński, Marcin (Leśne Prace Badawcze, 2015)
This paper deals with the market segmentation of recreational forest services using the concept of “sensation seeking” to describe expectations of town dwellers towards recreation. In this approach, the variable of landscape dissimilarity is evaluated based on the landscape preferences of town dwellers for recreational purposes. The urban agglomeration of Bialystok and the Knyszyn Forest (North-Eastern Poland) were chosen as the target for this case study. The results of the research suggest that the potential market of recreational forest services of the urban agglomeration of Bialystok includes and provides for about 30% of the inhabitants. The emerging true market of the recreational services of the Knyszyn Forest reaches only about 22% of the inhabitants of Bialystok. These market limitations and the characteristics of the forest landscape are inacceptable for outdoor recreation for the majority of town dwellers.